Evolutionary Ecology of Marine Invertebrate Larvae 2017
DOI: 10.1093/oso/9780198786962.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Latent Effects: Surprising Consequences of Embryonic and Larval Experience on Life after Metamorphosis

Abstract: The coming years will apparently bring increases in seawater temperatures, salinity fluctuation, and ocean acidity, along with increasing pollution levels and increasing incidences of coastal hypoxic events. We can also expect to see shifting patterns of phytoplankton abundance and nutritional quality. Many such stresses experienced early in development—even among brooded embryos—have been found to influence growth rates, survival, and other fitness characteristics following metamorphosis, sometimes for months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 98 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…This plasticity would help larvae adapt rapidly to a specific environment before altering genetics (Longa, 2019). Larvae exposed to OA were more capable of optimally regulating internal water balance and osmotic homeostasis to allow cells to proliferate and differentiate, in which DNA methylation may potentially be involved (Covelo-Soto et al, 2015;Pechenik, 2017).…”
Section: Phenotypic Plasticity To Oa Exposure and Natural Environment...mentioning
confidence: 99%
See 1 more Smart Citation
“…This plasticity would help larvae adapt rapidly to a specific environment before altering genetics (Longa, 2019). Larvae exposed to OA were more capable of optimally regulating internal water balance and osmotic homeostasis to allow cells to proliferate and differentiate, in which DNA methylation may potentially be involved (Covelo-Soto et al, 2015;Pechenik, 2017).…”
Section: Phenotypic Plasticity To Oa Exposure and Natural Environment...mentioning
confidence: 99%
“…Several previous laboratory studies have shown that OA as a single stressor or OA combined with other environmental stressors can reduce (Bryne et al, 2019;Byrne & Przeslawski, 2013;Espinel-Velasco et al, 2020;Ko et al, 2014;Ross et al, 2016) or improve (Bryne et al, 2019;Lim et al, 2020;Ross et al, 2016) growth, metabolism, calcification and survival of several economically important and edible mollusc species, especially oysters. While these studies have focused on a single life stage, the consequences of OA can result from carry-over effects, in which prior experience of stress exposure in one life stage can be passed onto the next life stage (Pechenik, 2006(Pechenik, , 2017. For example, the low pH (7.7-7.8) experienced during the larval stage did not affect the growth and shell structure of the Pacific oyster, Crassostrea gigas, in the Yellow Sea (Ko et al, 2013) but deteriorated the growth of the estuarine Olympia oyster, Ostrea lurida (Hettinger et al, 2012), Sydney Rock oyster, Saccostrea glomerata, and C. gigas from New South Wales (Parker et al, 2009) during their juvenile stages.…”
Section: Introductionmentioning
confidence: 99%
“…Metamorphosis does not promise a new beginning: embryonic and larval experiences can be expressed latently in juvenile and adult quality (Emlet & Sadro, 2006 ; Pechenik, 2006 ). Food limitation and prolonged planktonic duration have been shown to negatively influence juvenile size, growth, and survival (reviewed in Pechenik, 2018 ). In facultative planktotrophs, larval feeding resulted in larger juveniles in echinoderms (Allen & Podolsky, 2007 ; Emlet, 1986 ; Hart, 1996 ) and gastropods (Kempf & Hadfield, 1985 ; Miller, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metamorphosis does not promise a new beginning: embryonic and larval experiences can be expressed latently in juvenile and adult quality (Emlet & Sadro, 2006;Pechenik, 2006). Food limitation and prolonged planktonic duration have been shown to negatively influence juvenile size, growth, and survival (reviewed in Pechenik, 2018).…”
mentioning
confidence: 99%